HIV/AIDs and food and nutrition security: from evidence to action - Gillespie, Stuart; Kadiyala, Suneetha (International Food Policy Research Institute, 2005)
The HIV/AIDs pandemic is a global crisis with consequences that will be felt for decades to come. Thirty-nine million people are currently infected with the virus, including more than 25 million from Sub-Saharan Africa. Many millions are affected in different ways. The ability of households and communities to ensure their own food and nutrition security is increasingly being threatened. With the most detailed evidence base yet assembled, this review systematically maps our growing knowledge of the interactions between HIV/AIDS and food and nutrition security, pointing to where and how future policy needs to change to remain relevant and effective.